Pendampingan Pembuatan Artikel Ilmiah Bagi Mahasiswa Pendidikan Fisika STKIP Nurul Huda - Widayanti, Widayanti; Sinensis, Arini Rosa; Firdaus, Thoha; Effendi, Effendi; Rofiqah, Siti Anisatur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
Mentoring aims to direct students to write scientific articles properly and systematically. the method of implementing the service through several stages including: preparation, implementation, monitoring and evaluation of activities. Mentoring is carried out at the Teacher Training and Educational Sciences College (STKIP) Nurul Huda. The results of assistance in preparation for the problems faced by students, students do not understand the writing and systematics of scientific articles. Furthermore, the implementation of students is directed through the material presented to make scientific articles. the next stage is monitoring students in offline monitoring and daring to write blind scientific articles. Furthermore, the evaluation stage is carried out through the presentation of scientific articles and analysis of constraints and supporting activities for writing scientific articles. Constraints students find it difficult to find references to scientific articles and difficulties in determining the title. However, these obstacles can be overcome with the assistance and direction provided.